Investigating the emotional content of older adults engaging in a fall prevention exercise program integrated with dance movement therapy: a preliminary study - Pitluk Barash, Michal; Elboim-Gabyzon, Michal; Shuper Engelhard, Einat (Frontiers in Psychology, 2023)
Fall prevention interventions for older adults have primarily focused on the physical aspects, overlooking the emotional aspects inherent in falls. This qualitative study presents a novel fall prevention intervention that integrates physical therapy exercise (PTE) based on the Otago Exercise Program with Dance Movement Therapy (DMT) to address the emotional experience during PTE. The aim of this study is to explore the emotional content expressed by older adults during balancefocused exercises and the unique emotional content expressions following the PTE+DMT intervention compared to the PTE intervention. Eleven older adults (aged 81-91 years) from a day center were randomly assigned to either the PTE+DMT group (n = 6) or the PTE group (n = 5). Interpretative phenomenological analysis of the instructors' observations and process diary identified three themes that emerged during the sessions: (1) self-image and self-worth, (2) the individual in relation to others, and (3) past memories. These themes highlight both similarities and differences between the groups. These findings provide valuable insights into the emotional experiences encountered by older adults, particularly in the context of falls prevention practices. Recognizing, understanding, and facilitating the expression of these experiences can enhance the effectiveness of fall prevention interventions and contribute to the overall health of older adults.